SISTEM PARKIR OTOMATIS MENGGUNAKAN RFID BERBASISKAN MIKROKONTROLER AT 89S51 - Winarsih, Irda; Mahendra, Reza (Jurnal Teknik Elektro, 2009)
The Automatic Parking System is a system which automatize park of the car where we do notneed wasting our time in searching for a vacant place parking the car. Only with the RFIDtag touch hence our car will be parked automatically in place which we have determinedpreviously. This appliance use a microcontroler AT89S51 as controller brain, RFID card asidentification of the car owner, and some base lifts which made and designed in a such waycould move freely and basically driven by electric motors. In this system, microcontroller isused to arrange and control the movement and the position of car contained base lifts to beparked. After being identified the car ID by microcontroller and the driver has left the car,the system then started working until the parking process completed and the microcontrollerwill command the motor to return and move the empty base back the place ,standing by fornew process. The car retrieval process car happened on the contrary. The pallet liftmovement is motorized by four 12 VDC power motors gearbox.Keywords: Parking, Microcontroller, RFID, Motor gearbox.